Management of Root Like Man: Case from Gatot Soebroto, The Indonesian Army National Hospital - Sundoro, Ali; Supit, Laureen; Surachman, Asrofi S.; Adam, Harun; Budiman, Budiman; Guntoro, Guntoro (Jurnal Plastik Rekonstruksi, 2012)
Background: Patients and clinicians experience the frustration of cutaneous viral warts due to human papilloma virus (HPV) infection. Verruca vulgaris, the common warts, appear in various forms at different body sites. Over 118 types of papilloma virus have been identified. The most common cutaneous warts are caused by types 1, 2, 4, 27, 57, and 19 HPV. The rare cases of generalized warts around the world are suspected to be caused by type 2 HPV. There are many treatment modalities for this disease but none is 100% effective yet. Patient and Method :We report a 39-year-old male with generalized warts on various body parts (scalp, forehead, trunk, arms, lower leg and foot). The team consist of plastic surgeons, dermatologist, psychiatrist, pathologist, medical rehabilitationist, and internist. The treatment goals were to remove all warts, prevent recurrence of the disease, and improve the immunological status of the patient. Serial excisions were performed and closure attained using a combination of primary sutures, skin grafts (split- and full-thickness), and skin flaps. 5 Fluorouracil was administered on the raw surfaces before closure. Staged excisions were performed 11 times, with 3-4 weeks interval over a1-year period. Interferon and cimetidine injection were also given to augment the immune system.Results : All lesions were successfully excised and reconstructed. On a few fingers, hypertrophic scar and minor contracture ensued after closure by skin graft. Patient is able to carry out daily living activities independently. Patient was profoundly delighted and his quality of life improved.Summary : Management of a rare generalized verruca vulgaris through a team approach, by multiple staged excision, 5-FU application before defect closure, combined with antiviral therapy, proved effective in a case.